Makna Ungkapan Sarkasme Dalam Komunikasi Sosial Pada Dialek Menu-Meni - Sutarman Sutarman (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2019)
This research is a qualitative research which aims to explain the meaning of the sarcasm of expression that is often used in social communication in the Menu-Meni dialect. The method used in this study is the method of field linguistics and literature. In collecting data, researchers used observation and interview techniques. The method used in analyzing data is an interactive model that consists of selecting data, presenting data and verifying data. The results showed that the meaning of the expression of sarcasm is not always negative in communication but it can be positive. The meaning of the expression sarcasm in communication in Meni dialect is the meaning of closeness, the meaning of innuendo, the meaning of insults and the meaning of anger.